Comparative Study on Nutritional Importance of Cow, Camel and Goat Milk of Nangarhar Province, Afghanistan - , AssistantProf.Hedayetullah; Prof. Gulahmad Sohail; Prof. Jamaat Khan Hemat (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Milk is a dispersed complex colloidal solution containing fats, Protein, water, minerals and some other compounds. Specific gravity of milk is defined as a density of milk per density of water with same volume.As the milk is a complete food, the assessment of its nutritive value valuable.The comparisonof 20 samples of cows, camels and goats milks regarding to physical and chemical parameters including: pH , Proteins, Fats and specific gravity.The research has been done in Nangarhar Province, Khatiz Diary Process Factory from February 2019 to Jun 2019 on pH, protein, Fat, Specific gravity, chemical and physical parameters and analysis of cow, camel, and goat's 20 samples of milk in Khatiz Dairy Process factory. Based on the research, cow's milk has the following amount of ingredients. pH is 6.75‌, protein 3.5%, Fat 4.62%, Specific gravity1.050. Camel's milk has the following amount of ingredients. pH is 6.75, protein 3.42%, Fat 4.3%, Specific gravity1.030, Goat's Milk has the following ingredients pH is 6.75, proteins 4.82%, Fat 6.73% and  Specific gravity 1.050.Comparing the result of above 3 types of milk of 3 different cattle’s, we come to know that goats' milk is more enriched with protein and Fat than cow and camel's milk. That is the reason why goats' milkis traditionally recommended in rural areas and villages for kids suffering from malnutrition. On the other hand, based on medical research camel's milk are recommended for patients suffering from cancer.